Ion Exchange Equilibria Involving uni-Univalent, uni-Bivalent Exchange Systems to study Effect of Ionic Charge on Equilibrium Constant - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
The ion exchange reactions for Cl-/I- and Cl-/SO42- systems were studied to determine the equilibrium constant (K) at different temperatures from 30.0° to 45°C. For Cl-/SO42-exchange, the value of K observed at 30°C was 20 which was higher than K value of 16.7 for Cl-/I- exchange at the same temperature. This difference in K values was due to the ionic charges of ions in solution.